2008
DOI: 10.1038/npp.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Enhances Reactivated Fear Memories

Abstract: Although ethanol has been shown to impair acquisition of memory, its effect on consolidated memories is not clear. Recent reports revealed that memory retrieval converted consolidated memory into a labile state and initiated the reconsolidation process. In the present study, we have demonstrated the effect of ethanol on reactivated fear memory. We used contextual fear conditioning where rats were conditioned with mild footshock, re-exposed to the training context for 2 min, immediately injected with ethanol or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
5
23
0
1
Order By: Relevance
“…In various training paradigms, strychnine, glucose, amphetamine or ethanol injections, when administered just after reactivation, have been shown to increase retention performance 24 or 48 h later. (Gordon and Spear 1973b;Rodriguez et al 1999;Blaiss and Janak 2006;Nomura and Matsuki 2008). Similar results have been obtained with more specific treatments, such as activating protein kinase A within the amygdala (Tronson et al 2006) or NMDA receptors (Lee et al 2006).…”
Section: Reactivation Allows the Facilitation Of Well-consolidated Mesupporting
confidence: 72%
“…In various training paradigms, strychnine, glucose, amphetamine or ethanol injections, when administered just after reactivation, have been shown to increase retention performance 24 or 48 h later. (Gordon and Spear 1973b;Rodriguez et al 1999;Blaiss and Janak 2006;Nomura and Matsuki 2008). Similar results have been obtained with more specific treatments, such as activating protein kinase A within the amygdala (Tronson et al 2006) or NMDA receptors (Lee et al 2006).…”
Section: Reactivation Allows the Facilitation Of Well-consolidated Mesupporting
confidence: 72%
“…Taking into account the absence of an emotive charge in our paradigm and the doses selected, we wondered if this type of modulation during re-stabilization would induce a memory enhancement, as has been shown in other reports (Nomura and Matsuki, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, in this case, the effect of the drug did not differ between high-and low-anxiety rats. Interestingly, based on the well-known pharmacological actions of ethanol as a positive modulator of GABA A receptors (Lister, 1987;Weiss and Porrino, 2002), a recent study showed that ethanol, administered after the reactivation of a contextual fear memory, enhanced the performance of treated animals at testing (Nomura and Matsuki, 2008). Moreover, this effect appeared to be mediated by the GABAergic system because the administration of picrotoxin, a GABA A receptor antagonist, inhibited the memory enhancement produced by ethanol.…”
Section: Introductionmentioning
confidence: 96%
“…The memory retrieval and testing sessions consisted of exposing the mice to the condi-1 tioning chamber for 5 min in the absence of a footshock. All sessions were performed between 8 a.m. and 11 a.m., and each session was video-recorded for automatic scoring of freezing, according to a previously described method (Nomura and Matsuki 2008). Fear memory was assessed and expressed as the percentage of time the animal remained frozen-a commonly used parameter for measuring conditioned fear in mice.…”
mentioning
confidence: 99%